Barefoot running training: Implications for joint stiffness and muscular co-activation - Tam, N.; Diveka, N. V.; Lamberts, R. P.; Tucker, R.; Hill, J. L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
To determine the influence of barefoot training on neuromuscular w-activation of lower limb muscles on variables associated with injury risk during running. Trained shod runners (n=23) participated in a barefoot running program. Joint stiffness, agonist: antagonist co-activation and the co-activation index were calculated. A progressive barefoot training program induces longer co-activation of the shank complex and lower ankle stiffness in the barefoot condition. Footwear is implicated in changing injury risk factors whether soft tissue or bony related injuries. This paper suggests barefoot training as an avenue for rehabilitating ankle injuries as it promotes an even distribution of joint stillness and lower ankle stiffness when compared to shod running.